Liberalizing Capital Flows and Managing Outflows. (Policy Papers; Policy Paper, 2012)
This is the fourth in a series of Board papers developing a comprehensive Fund view on capital flows and the policies that affect them. A first paper in December 2010 dealt with the Fund's overall role in this area, both historically and prospectively. The second paper in March 2011 developed a framework for policy advice on managing capital inflows broadly endorsed by the Board, which constitutes a first round articulation of the Fund's institutional views on managing capital inflows. The third paper in November 2011 examined the multilateral aspects of policies affecting capital flows, and focused mainly on source country policies. This paper covers liberalizing capital flows and the management of outflows.